2012
DOI: 10.1260/0263-6174.30.7.579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnetic Halloysite Composites for the Effective Removal of Tetracycline Hydrochloride from Aqueous Solutions

Abstract: Herein, we explain an effective method for the synthesis of halloysite/CoFe 2 O 4 magnetic composites (magnetic halloysite nanotubes or MHNTs) and their use as as adsorbents to effectively remove tetracycline hydrochloride (TC-HCl) from aqueous solutions. The synthesized composites were characterized by the following methods: Fourier transform infrared, X-ray diffraction, transmission electron microscopy, vibrating sample magnetometry and atomic absorption spectrometry. Our study results indicated that MHNTs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…In fact, due to the tubular structure and multiple surface groups, HNTs have gradually found many other applications for contaminant adsorption/degradation. As listed in Table 4, the adsorption/degradation of tetracycline, [96][97][98][99][100] ammonium ions, 101-104 2,4-dichlorophenoxyacetic acid, 105 chloroanilines, 106 phenol-based contaminant 107,108 5-aminosalicylic acid, 109 etc. by HNT-based composites from aqueous solutions has been reported.…”
Section: Other Hnt-derived Applications For Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, due to the tubular structure and multiple surface groups, HNTs have gradually found many other applications for contaminant adsorption/degradation. As listed in Table 4, the adsorption/degradation of tetracycline, [96][97][98][99][100] ammonium ions, 101-104 2,4-dichlorophenoxyacetic acid, 105 chloroanilines, 106 phenol-based contaminant 107,108 5-aminosalicylic acid, 109 etc. by HNT-based composites from aqueous solutions has been reported.…”
Section: Other Hnt-derived Applications For Water Treatmentmentioning
confidence: 99%
“…The tunable nanoshell thickness would affect the saturation adsorption capacity for tetracycline and the largest saturation adsorption capacity appeared at a thickness of 35 nm. Wang et al 97 also reported a magnetic HNT-based composite of HNTs/CoFe 3 O 4 for the removal of tetracycline hydrochloride from aqueous solutions. The authors investigated the effects of pH, temperature, initial concentrations and reaction time on the adsorption capacity for tetracycline hydrochloride.…”
Section: Other Hnt-derived Applications For Water Treatmentmentioning
confidence: 99%
“…A novel and quick method for selective adsorption of dibenzothiophene from gasoline using magnetic molecularly imprinted polymers as the adsorbent has also been described previously (Huang et al 2012). Moreover, an effective method for the synthesis of halloysite/CoFe 2 O 4 magnetic composites (magnetic halloysite nanotubes) and their use as adsorbents to effectively remove tetracycline hydrochloride from aqueous solutions has recently been explained (Guan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The removal of water pollutants using nanomaterials has become a very promising alternative due to the advantages exhibited by these nano-scale crystals compared with traditional methods of remediation. These advantages include high adsorption capacity per unit mass, absence of degradation by-products, environmental friendliness, capability for tailoring of the surface chemistry and the possibility of recovering the nanocrystals using an external magnetic field (Raven et al 1998;Liang et al 2010;Wang et al 2010;Zhang et al 2010;Giraldo and Moreno-Piraján 2012;Guan et al 2012;Atta et al 2013).…”
Section: Introductionmentioning
confidence: 99%